The Influence of Level of Understanding, Perception and Tax Fairness of Micro, Small and Medium Enterprises (UMKM) on Tax Obligations - Sri Ayem; Richi Hartina Sari (Jurnal Ilmu Manajemen Profitability, 2023)
This study was conducted to prove that a good level of understanding occurs because of the perception and fairness of taxes and tax obligations to do so. The main reason for MSME members in understanding the perception of tax justice is in good MSME tax obligations. Thus, we will analyze tax liability as a variable that is influenced by the variables that influence it, namely the level of understanding, as well as an additional variable, namely the perception and fairness of taxes for Micro, Small and Medium Enterprises (MSMEs). The population is the Yogyakarta MSME business actors. The sampling method is using convenience sampling. The total respondents are 46 respondents. Methods of data collection using a questionnaire via google form. The results showed that the level of understanding had a positive effect on tax obligations. Micro, Small and Medium Enterprises (MSMEs) tax perceptions and fairness have a positive effect on tax obligations. The level of understanding has a positive effect on tax obligations through tax perceptions and fairness of Micro, Small and Medium Enterprises (MSMEs). The implication of this research proves that the level of understanding of taxation is one element that plays an important role in the growth of organizational performance in MSMEs in Yogyakarta